2004
DOI: 10.1242/jcs.01079
|View full text |Cite
|
Sign up to set email alerts
|

A novel isoform of sarcolemmal membrane-associated protein (SLMAP) is a component of the microtubule organizing centre

Abstract: The microtubule organizing centre (MTOC) or the centrosome serves a crucial role in the establishment of cellular polarity, organization of interphase microtubules and the formation of the bipolar mitotic spindle. We have elucidated the genomic structure of a gene encoding the sarcolemmal membrane-associated protein (SLMAP), which encodes a 91 kDa polypeptide with a previously uncharacterized N-terminal sequence encompassing a forkhead-associated (FHA) domain that resides at the centrosome. Anti-peptide antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 47 publications
3
57
0
Order By: Relevance
“…Consistent with their localization, the STRIPAK complex from these two species has been reported to play roles in mitosis (9,12,20). Our failure to detect localization of the yeast Far complex components and even the Far9 truncation mutant without its tail-anchor domain to the spindle pole body is consistent with the hypothesis of Frost et al (9) that the function of the STRIPAK complex may have been "repurposed" and the S. cerevisiae STRIPAK complex has lost its function in mitosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with their localization, the STRIPAK complex from these two species has been reported to play roles in mitosis (9,12,20). Our failure to detect localization of the yeast Far complex components and even the Far9 truncation mutant without its tail-anchor domain to the spindle pole body is consistent with the hypothesis of Frost et al (9) that the function of the STRIPAK complex may have been "repurposed" and the S. cerevisiae STRIPAK complex has lost its function in mitosis.…”
Section: Discussionsupporting
confidence: 90%
“…Human SLMAP and the S. pombe STRIPAK complex also localize to the centrosome and the spindle pole body, respectively (9,12,20). Consistent with their localization, the STRIPAK complex from these two species has been reported to play roles in mitosis (9,12,20).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…1B). These Trabid-interacting proteins are known components of the STRIPAK (Striatin-interacting phosphatase and kinase) complex and include the Striatin family of WD40 domain proteins that function as regulatory subunits of protein phosphatase PP2A; factors that regulate cortical actin cytoskeleton dynamics: cortactin-binding protein 2, CTTNBP2NL, and FAM40A; and the centrosome-associated protein SLMAP (32)(33)(34). Interestingly, we did not find any PP2A subunits in the Trabid IPs, suggesting mutually exclusive or transient association of subcomplexes of STRIPAK to Trabid and PP2A (33).…”
Section: Identification Of E3 Ubiquitin Ligase Hectd1 In a Trabidmentioning
confidence: 99%
“…To test this and to further validate our antibody, we also transfected COS-7 cells with a myc- phosphatase and kinase (STRIPAK) complex, which has been described as possessing roles in multiple cellular processes, including signaling, trafficking, cell migration, and cardiac function (18). Previous reports have shown that Slmap is involved in microtubule organization (19), myoblast fusion (20), and excitation-contraction coupling (21). It has also been reported that mutations in SLMAP may give rise to Brugada syndrome (22).…”
Section: Introductionmentioning
confidence: 99%